2012
DOI: 10.1044/1092-4388(2012/11-0131)
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Speech to Children Based on Their Perceived Phonetic Accuracy

Abstract: Purpose We examined the relationship between adults' perception of the accuracy of children's speech, and acoustic detail in their subsequent productions to children. Methods Twenty-two adults participated in a task in which they rated the accuracy of 2- and 3-year-old children's word-initial /s/and /∫/ using a visual analog scale (VAS), then produced a token of the same word as if they were responding to the child whose speech they had just rated. Result The duration of adults' fricatives varied as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
1
24
0
2
Order By: Relevance
“…Our underlying assumption was that use of a continuous measurement tool such as VAS should enable listeners to provide a more nuanced description of the fine phonetic characteristics of children’s speech than would be possible with a discrete measure, such as an identification task. Previous work found support for this assumption by showing that VAS ratings of productions of /s/ and /ʃ/, averaged across a group of listeners, strongly correlated with the acoustic parameter of centroid frequency (Julien & Munson, 2012; Munson, Johnson, & Edwards, 2012). However, based on their analysis, we cannot infer anything about the responses of individual listeners.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our underlying assumption was that use of a continuous measurement tool such as VAS should enable listeners to provide a more nuanced description of the fine phonetic characteristics of children’s speech than would be possible with a discrete measure, such as an identification task. Previous work found support for this assumption by showing that VAS ratings of productions of /s/ and /ʃ/, averaged across a group of listeners, strongly correlated with the acoustic parameter of centroid frequency (Julien & Munson, 2012; Munson, Johnson, & Edwards, 2012). However, based on their analysis, we cannot infer anything about the responses of individual listeners.…”
Section: Discussionmentioning
confidence: 80%
“…Average judgments of naïve listeners have two additional benefits. First, they are ecologically valid, as they presumably predict the cumulative feedback that children receive from members of the language community during social interactions, a claim that is developed in more detail in Julien and Munson (2012). Second, they can be used as continuous measures when a suitable acoustic or articulatory measure does not exist.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our speculation about how listeners might perceive the productions analyzed by Macken and Bartonis based on the results of numerous studies that elicit continuous ratings of children’s productions of sounds (Julien & Munson, 2012; McAllister Byun, Halpin, & Harel, 2015; Munson & Brinkman, 2004; Munson, Johnson, & Edwards, 2012; Munson, Schellinger, Edwards, Beckman, & Meyer, 2010; Strömbergsson, Savli, & House, 2015). These studies have shown that listeners are capable of providing continuous ratings of children’s productions, provided that the productions themselves vary continuously in how closely they resemble canonical productions of sounds.…”
Section: The Auditory-perceptual Assessment Of (Not-so-)covert Contrastmentioning
confidence: 99%
“…Parent response to child production varies dependent upon whether or not the production is perceived as phonetically accurate versus inaccurate (Julien & Munson, 2012) and familiar versus non-familiar (Olson & Masur, 2012).…”
Section: Tracking Vocal Developmentmentioning
confidence: 99%